Desain Pembelajaran Pendidikan Islam Berbasis Neurosains: Peran Musik, Pencahayaan dan Tata Ruang - Tian Khusni Akbar; Suyadi Suyadi (UMSU, 2021)
This study aims to analyze the design of Islamic educational learning through the art of music, lighting and spatial neuroscience perspectives. This is important because Islamic education has not yet maximized innovative learning methods in using the learning model. This research approach is qualitative type of literature. The data sources of this study are literature in the fields of music, spatial lighting, Islamic education and neuroscience. The collected data is then analyzed qualitatively using inductive thinking patterns. The results showed that the design of learning through music is able to optimize human brain function in both emotions, motivation, to positive actions, because the right and left brains functioning means that the cognitive and psychomotor aspects function optimally. Optimization of lighting in the study room has a great effect on the brain because most of the human brain receives information / knowledge through the human eye. Spatial design in learning is the optimization of the learning room in order to provide a sense of security and comfort in the learning process.